EXTERNAL TRADE AGROINDUSTRIJAL PRODUCT OF SERBIAN AND CROATIAN - Kuzman, Boris; Ivić, Milenko; Dumonjić, Bojan (Economics of Agriculture, 2011)
As foreign trade exchange of agricultural products and trade liberalization shows advantages it expresses many aggravating circumstances and risks. Process of trade liberalization means tough competition for food producers in Serbia. It implies necessity of technological level production raising, productivity raising, effciency raising and implementation of marketing management. High level of competition needs to enable increasing of goods quality and offer. It is real to expect that costs of products be lower, what can cause problem to domestic producers by decreasing their income. But, this process enables customers to buy more different products in lower costs. The exploring subject of this research is foreign trade exchange of agricultural products of Serbia with republic of Croatia CEFTA, according to free trade agreement. This agreement enables West Balkan to become economically integrated area which represents remarkable destination for foreign investments. The goal of this research is to perceive possibilities of improvement and expanding of foreign trade exchange of agricultural products of Serbia in Republic of Croatia. Method of scientifc work and data source: In this work there is going to be used standard statistical and mathematical methods. Also, there is going to be used analysis of accepted data contents and results of previous researches. As data resources there are going to be used Foreign Trade Offcial Statistics, Ministry of Agriculture articles, Chamber of commerce articles and other relevant sources. Period from 2004 to 2008 is enclosed with this research.